Digitalization and direct democracy: directed by whom? - Losano, Mario G. (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
The recent political “movements” present itself as an alternative to the traditional political parties and propose the direct democracy as an alternative to the representative democracy. In Italy too, the “Movimento 5 Stelle” followed this path and gathered a considerable electoral success. Francesco Pallante, an Italian public law professor, analyses critically this present conception of direct democracy in his book Contro la democrazia diretta (Against direct democracy 2020), stepping stone of the present article. More specifically, the digitalization is presented today as the technical support of direct democracy and, in Italy, the “Movimento 5 Stelle” entrusts to the “Piattaforma Rousseau” the interchange with its affiliates. The present article expresses the doubts about this platform - doubts now arousing also among the same Movimento. In fact, on the one side, the platform is property of a private corporation, which is separate and independent from the Movimento; on the other side, the “Piattaforma Rousseau” was twice sanctioned by the “Garante della Privacy”, because the platform does not sufficiently protect neither the privacy of the militants, nor the secrecy of the vote. This article was submitted on August 31th, 2020, to the journal “Diritto dell’informazione e dell’informatica”, and was rejected for being “political” - a case of straightforward censorship. The text of August 31th, 2020, –which is here translated without any change– is followed by an update upon the increasing number of interventions aimed to limit the freedom of press and the freedom of speech in Italy. This repressive attitude seems to progressively establishing itself worldwide.